Penerapan Metode Khusus Pendidikan Agama Islam Bagi Anak (analisis Psikologi Perkembangan Anak) - Wafa', Muhammad (Literasi: Jurnal Ilmu Pendidikan, 2023)
This paper discusses the application of several methods in Islamic religious education, with an analysis of Child Development Psychology. And what aspects are contained therein. This study uses the type of library research/ library research, which collects various data and information from the library. Descriptive-analytic which is the nature of the research. The description in the text is as it is, what is meant in the text is conveyed by phrasing the text. While the data is processed by content analysis. The methods of Islamic education that can be taken and then applied are the exemplary method, the method of advice, the method of punishment, and the method of promises and threats. The application of these methods can be a means of transforming children through the educational process. Age and child psychological development are one of the considerations in determining the application of Islamic educator methods. Islamic education can be said to be successful if the learning process, the methods used and the results of education are in accordance with Islamic teachings/law.Keywords: Method, Education, Islamic Religion, Psychology